2010
DOI: 10.1007/s10059-010-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Melittin Suppresses PMA-Induced Tumor Cell Invasion by Inhibiting NF-κB and AP-1-Dependent MMP-9 Expression

Abstract: Matrix metalloproteinase-9 (MMP-9) plays an important role in the invasion and metastasis of cancer cells. In this study, we examined the inhibitory effect of bee venom (BV) and its major peptides, melittin and apamin, on PMA-induced invasion induced by MMP-9 expression in Caki-1 renal cancer cells. BV and melittin, but not apamin, significantly suppressed PMA-induced invasion by inhibiting MMP-9 expression in Caki-1 cells. Furthermore, as evidenced by MMP-9 promoter assays, melittin inhibited MMP-9 gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 38 publications
4
58
0
1
Order By: Relevance
“…PMA increased expression and the enzymatic activity of MMP-9, whereas MMP-2 expression was not affected by PMA. Although we did not compare the basal expression levels and the activities of either MMP-2 or -9 in A549 and HeLa cells, our results support a previous report that MMP-2 is constitutively overexpressed in metastatic cancer cells (7). We also found that Trolox inhibits PMA-induced expression and the proteolytic activity of MMP-9 in both cancer cells.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…PMA increased expression and the enzymatic activity of MMP-9, whereas MMP-2 expression was not affected by PMA. Although we did not compare the basal expression levels and the activities of either MMP-2 or -9 in A549 and HeLa cells, our results support a previous report that MMP-2 is constitutively overexpressed in metastatic cancer cells (7). We also found that Trolox inhibits PMA-induced expression and the proteolytic activity of MMP-9 in both cancer cells.…”
Section: Discussionsupporting
confidence: 68%
“…MMP-2 is highly expressed in metastatic cancers (7). MMP-9 is also up-regulated in metastatic cancer cells and is implicated in a wide range of pathologic conditions, including inflammation and tissue repair (5).…”
Section: Trolox Inhibits Pma-induced Ros Generation In Lung and Cervimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used in oriental medicine for many years to treat inflammatory diseases 8) , and in Korean medicine in pharmacopuncture to treat back pain, rheumatism, and many skin diseases due to its antibacterial, antiviral, and anti-inflammatory effects 9,10) . BV consists of a complex mixture of proteins, peptides, and low molecular weight components.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…BV increases pro-apoptotic proteins by increasing the expression of death receptor (DR) in the cell surface and simultaneously inhibiting the activity of anti-apoptosis factors [11][12][13][14] . Several experimental studies have demonstrated that BV and/or melittin have anti-cancer effects 9,10,15) . Additionally, it has been reported that BV enhances the cytotoxic effects of NK cells on human lung cancer and acts synergistically with NK cells to inhibit cancer cell growth 16,17) .…”
Section: ⅰ Introductionmentioning
confidence: 99%